Factor by grouping.
For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=2⋅-3=-6 and whose sum is b=-1.
Factor -1 out of -a.
Rewrite -1 as 2 plus -3
Apply the distributive property.
Factor out the greatest common factor from each group.
Group the first two terms and the last two terms.
Factor out the greatest common factor (GCF) from each group.
Factor the polynomial by factoring out the greatest common factor, a+1.
Simplify the denominator.
Rewrite 4a2 as (2a)2.
Rewrite 9 as 32.
Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=2a and b=3.
Cancel the common factor of 2a-3.
Cancel the common factor.
Rewrite the expression.